PENGARUH PERTUMBUHAN PENJUALAN TERHADAP NILAI PERUSAHAAN DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING - I Gusti Ngurah Satria Wijaya (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2019)
The tight competition that arises requires companies to further improve their performance and innovate with their products. To improve performance and product innovation, companies need more funds. This has become one of the factors for companies to enter the stock exchange or often called go public. Companies must be managed properly in order to increase the value of the company through financial or funding decisions. Based on this background, this study aims to examine the effect of sales growth on firm value with capital structure as an intervening variable on the Indonesia Stock Exchange. The data used in thisstudy are secondary data originating from telecommunications sector companies in the Indonesia Stock Exchange. The analysis technique used in thisstudy is multiple linear regression and sobel analysisforthe effect of indirect factors. The results of thisstudy are Sales Growth has no significant positive effect on Company Values,Capital Structure has a significant positive effect on Company Values, and theCapital Structure is not able to mediate the influence between SalesGrowth andCompanyValue.